An Epidemiological Study of Drug Resistance and Resistance Genes in Bovine Escherichia coli Isolates in Heilongjiang Province of China - Zheng, Jia-San; Zhu, Ting-Ting; Liu, Yun; Liu, Ting; Li, Yan-Qing; Zhang, Zhen; Shi, Dong-Fang; Bao, Jun; Yu, Li (Acta Scientiae Veterinariae, 2018)
Background: To explore the epidemiology of bovine multidrug-resistant Escherichia coli isolates and resistance genes in Heilongjiang province of China. This study examined the prevalence of genes in bovine E. coli isolates, which confer resistance to antibiotics that are commonly used in the clinic, in regions of Baiquan, Shangzhi, and Songbei of Harbin. The purpose of the study was to investigate the epidemiology of the main resistance genes of bovine E. coli isolates in clinical veterinary medicine, and to provide a theoretical basis for preventing the spread of drug-resistant bacteria, as well as for rational drug use. Materials, Methods & Results: The sensitivity of 105 isolates to 22 antibiotics was determined using the KirbyBauer disk diffusion method, and the distribution of 19 kinds of common drug resistance genes was investigated using Polymerase Chain Reaction. The results showed that the resistance rate to nine antibiotics was over 50%, including rifampin (84.76%), ampicillin (73.58%), tetracycline (69.52%), and sulfisoxazole (59.05%). In total, 105 strains of bovine E. coli presented 21 spectra of drug resistance, including eight strains (7.62%, 8/105) that were resistant to one antibiotic and four strains (3.81%, 4/105) that were resistant to 21 antibiotics. The resistance gene detection results showed that the streptomycin-resistance gene strA was found in 73 isolates, accounting for 69.52% of the isolates, followed by the sulfanilamide-resistance genes sul3/sul2 and the aminoglycoside-resistance gene aphA, which accounted for 57.14%, 51.43%, and 50.48%, respectively, of the isolates. Discussion: This study revealed serious drug resistance of bovine E. coli isolates in some areas of Heilongjiang province. Of 105 E. coli isolates, more than 50% were resistant to the following antibacterial drugs: rifampicin, ampicillin, tetracycline, sulfisoxazole, and cephalothin. The isolates were the most sensitive to amikacin, with a sensitivity of 84.76%, followed by sensitivity to ofloxacin, ciprofloxacin, norfloxacin, cefoxitin, and tobramycin. Drug sensitivity tests showed that the drug resistance spectra of the bovine E. coli isolates was different in different regions, indicating that there were multidrug-resistant bovine E. coli isolates in different regions of Heilongjiang province, and that drug resistance differed among different regions. This may be due to prolonged use or overuse of antibiotics in a particular locality. Additionally, because of different management modes of livestock farms, the application of antimicrobial drugs in some farms may have imposed selective pressure on the intestinal flora including E. coli, resulting in the horizontal transmission of drug resistance among the bacteria. The study found that some strains had a resistance phenotype, but no resistance gene, while some had a resistance gene without expressing a resistance phenotype, which is consistent with relevant reports in the literature. This may be related to the same genotype corresponding to different resistance phenotypes, or different levels of gene expression, or different drug metabolic rates. In our study, some strains with certain drug resistance genes were sensitive to the corresponding drug, which may be due to mutations of drug-resistance genes, the loss of a strains resistance phenotype, or the loss of gene function. These issues require further study. This study revealed serious drug resistance of bovine E. coli isolates in some areas of Heilongjiang province. Of 105 E. coli isolates, more than 50% were resistant to the following antibacterial drugs: rifampicin, ampicillin, tetracycline, sulfisoxazole, and cephalothin. The isolates were the most sensitive to amikacin, with a sensitivity of 84.76%, followed by sensitivity to ofloxacin, ciprofloxacin, norfloxacin, cefoxitin, and tobramycin.